Comparative energy and exergy analysis of a subcritical cascade refrigeration system using low global warming potential refrigerants. (5th February 2021) - Aktemur, Cenker; Ozturk, Ilhan Tekin; Cimsit, Canan
Highlights: Low global warming potential refrigerants in CRS are studied. R41-RE170 performs better for use of CRS at low temperatures. The performance of R41-R423A in CRS is poorer than that of other refrigerant pairs. RE170 is proposed as alternative refrigerant to R423A in upper cycle. There is maximum COP improvement of 13.05% compared to studies in literature. Abstract: This study examines a variety of evaluation criteria such as various operating and design parameters for thermodynamic performance of a cascade refrigeration system (CRS). R41 is used in low-temperature circuit (LTC), whereas R1243zf, R423A, R601, R601A, R1233zd (E) and RE170 are used for the first time in this study and are adapted for a high-temperature circuit (HTC). This study with four aims are conducted: (1) to analyse refrigerant pairs with low global warming potential (GWP) to further contribute to the literature; (2) to investigate the impact of various operating parameters on system performance; (3) to suggest potential alternative refrigerant to R423A; (4) to also compare the performance of the refrigerant pairs used in this study with those analysed by researchers in the literature. The results demonstrate that condenser and evaporator temperature ranges have a significant effect on the performance parameters studied in the system designed for six refrigerant pairs. The greatest reduction in COP occurs in R41-R423A with about 43.85% in a change of 10°C in the condenser temperature. A change of 10°C in the evaporator temperature causes the COP of the CRS to rise by approximately 19% for all refrigerant pairs. For applications that desire low temperatures, R41-R423A exhibits the lowest COP and exergy efficiency with 1.105 and 33.93%, respectively, whereas R41-RE170 presents the highest COP and exergy efficiency with 1.210 and 37.18%, respectively. Furthermore, exergy destruction in HTC compressor is made up almost to one-third of total exergy destruction. RE170 is proposed as an alternative refrigerant for R423A by the reason of its low environmental detriment and superior performance. Furthermore, there is a maximum COP improvement of 13.05% compared to studies in the literature.